Gravidas with class III obesity: evaluating the abdominal skin microbiota above and below the panniculus*. (17th October 2016) - Edwards, Rodney K.; Kumar, Ranjit; Zhi, Degui; Szychowski, Jeffrey; Subramaniam, Akila; Lefkowitz, Elliot J.; Morrow, Casey
Abstract: Objective : We sought to compare the skin microbiota above and below the panniculus of third-trimester pregnant women with class III obesity. Methods : We collected swabs from the anterior panniculus and from the intertriginous area under the panniculus of women with class III obesity (body mass index ≥40 kg/m 2 ) carrying a live singleton at ≥28 weeks. DNA was extracted. PCR with primers targeting the 16S rDNA V4 region were used to prepare an amplicon library. PCR products were sequenced (Illumina MiSeq platform). The 16S rDNA sequences were processed, integrated, analyzed and reported using QIIME and in-house developed scripts. Taxonomy was assigned using RDP Classifier (threshold 0.8) against the Greengenes 16S rDNA database. Results : Twenty women were enrolled. One sample pair was excluded for low sequence depth. Using permutation testing, there was significantly less bacterial diversity in the samples above compared to below the panniculus (beta diversity using weighted UniFrac metrics; p  < 0.001). Conclusion : In pregnant women with class III obesity, the skin microbiota in the subpannicular fold differs from and is more diverse than that on the anterior panniculus.